Revealing the uniqueness of variations in prospective teachers' metacognitive activities in solving mathematical problems based on gender - Ramlah Ramlah; Tatag Yuli Eko Siswono; Agung Lukito (Jurnal Infinity, 2024)
A significant amount of scholarly investigation has recently focused on metacognitive activity. However, the examination of metacognitive variations in solving math problems that are still limited in scope. This case study examines gender differences in activity variations of metacognitive activities, specifically awareness, regulation, and evaluation, in prospective teachers solving mathematical problems based on mathematical models. Participants were selected through purposive sampling. Twelve male and sixteen female participants were chosen from those who participated in the 'capita selecta' mathematics course at a public university in West Java, Indonesia. The data were collected through mathematical problem-solving tasks and interviews. The results show that the variations in metacognitive activities between male and female participants are different. Females tend to be more complex and structured in their evaluation activities, while males tend to be more complex and structured in their awareness activities. Based on the results, recommendations are made for future studies.